Sports and Health: From Sick Care to Health Care - Helmi Salim, Ahmad Munawwar; Jamaluddin, Khairy; Aziz, Ramlan Abd (International Journal of Human and Health Sciences (IJHHS), 2024)
The symposium theme, "Sports and Health: From Sick Care to Health Care," explores the transition from a healthcare system primarily focused on treating illness to one that prioritizes preventive health measures through sports and physical activity. By examining the impact of physical activity on disease prevention, mental health, and community engagement, the discussion underscores the vital role of sports in promoting holistic health. Drawing on compelling research and real-world examples, the discussion navigates the intersection of sports and healthcare, emphasizing the need for integrated strategies in public health initiatives. Two renowned speakers and experts in both sports and health, will share inputs into how embracing sports as a fundamental component of healthcare not only mitigates illness but also fosters healthier, more vibrant societies. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S21